Corporate turnaround as knowledge subversion: a dialogic perspective on transformational change - Pillay, John (Cranfield University, 2013)
This research presents a knowledge-based perspective on corporate turnaround. In this research it is proposed that subverting existing knowledge is as much a part of the corporate turnaround process as other change management activities, a concept termed “dialogic knowledge subversion”. Conceptual development was supported by a literature review into change, knowledge, discourse and Bakhtinian theories. This theoretical investigation was further developed using two empirical studies. The first empirical work focused on the case study of an organisation which had turned itself around. Findings from fifteen interviews and a focus group workshop were gathered and analysed using story network architecture and dialogic concepts. The data was further developed with a second empirical study, which investigated corporate turnaround from the perspective of twelve expert practitioners. Findings from these studies were used to develop a model for knowledge subversion in corporate turnaround situations. There are a number of contributions to change management theory and practice offered by this investigation. The research finds that dialogic knowledge subversion is present and required in the process of corporate turnaround. Furthermore, practitioners use the breakdown of existing knowledge in the organisation to create the impetus for change and build momentum for the turnaround. Indeed the research suggests that experts regard knowledge subversion as essential to the change process and actively create the conditions where it thrives. A dialogic knowledge subversion model for corporate turnaround is proposed, which is a resource for change theorists and practitioners alike.